Performance of automated multiplex polymerase chain reaction (mPCR) using synovial fluid in the diagnosis of native joint septic arthritis in adults. (March 2019) - Sigmund, I. K.; Holinka, J.; Sevelda, F.; Staats, K.; Heisinger, S.; Kubista, B.; McNally, M. A.; Windhager, R.
Abstract : Aims: This study aimed to assess the performance of an automated multiplex polymerase chain reaction (mPCR) technique for rapid diagnosis of native joint septic arthritis Patients and Methods: Consecutive patients with suspected septic arthritis undergoing aseptic diagnostic joint aspiration were included. The aspirate was used for analysis by mPCR and conventional microbiological analysis. A joint was classed as septic according to modified Newman criteria. Based on receiver operating characteristic (ROC) analysis, the area under the ROC curve (AUC) values of the mPCR and the synovial fluid culture were compared using the z-test. A total of 72 out of 76 consecutive patients (33 women, 39 men; mean age 64 years (22 to 92)) with suspected septic arthritis were included in this study. Results: Of 72 patients, 42 (58%) were deemed to have septic joints. The sensitivity of mPCR and synovial fluid culture was 38% and 29%, respectively. No significant differences were found between the AUCs of both techniques (p = 0.138). A strong concordance of 89% (Cohen's kappa: 0.65) was shown. The mPCR failed to detect Staphylococcus aureus (n = 1) and Streptococcus pneumoniae (n = 1; no primer included in the mPCR), whereas the synovial fluid culture missed six microorganisms (positive mPCR: S. aureus (n = 2), Cutibacterium acnes (n = 3), coagulase-negative staphylococci (n = 2)). Conclusion: The automated mPCR showed at least a similar performance to the synovial fluid culture (the current benchmark) in diagnosing septic arthritis, having the great advantage of a shorter turnaround time (within five hours). Cite this article: Bone Joint J 2019;101-B:288–296.